Analisis Kemampuan Menyelesaikan Soal Cerita Pada Materi Perkalian Di Kelas II Sekolah Dasar - Ari Rizkiyanto; Veryliana Purnamasari; Ryky Mandar Sary (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2021)
This study aims to identify the ability to solve story problems on multiplication material in grade II elementary school. The research approach used is a descriptive qualitative approach. Data collection techniques in this study were tests and interviews. The instrument used was a test of the ability to solve the multiplication material story questions and interview guides. The test of the ability to solve the story questions used is in the form of an essay which consists of 4 questions. The data analysis used was technical triangulation. The results showed that: (1) the ability to write down the known aspects was 87,5% in the very good category. (2) the ability to write down the aspects being asked is 80% in the good category. (3) the ability to solve mathematical models is 67,5% in the good category. (4) the ability to draw conclusions is 62,5% in the sufficient category. Thus it can be interpreted that the better the achievement indicators possessed by students, the better the ability to solve the story questions.